DEFICIT DE COMMUNICATION INTERNE DANS LES INSTITUTIONS D’ENSEIGNEMENT SUPERIEUR ET UNIVERSITAIRE EN RDC : CAS DE L’UNIVERSITE LIBRE DE KISANGANI - ALIFI AMATCHO, Yves-Daddy (IJRDO - Journal of Social Science and Humanities Research, 2021)
Communication, a major component of social practice, is at the heart of life in society from a political, economic and social point of view. To this end, it contributes to strengthening the visibility of men and of various institutions. It is thus nowadays, companies, organizations, the various social structures use it in order to communicate their intentions, projects and activities in order to build an image accepted in the environment which surrounds it and ultimately create a thread of dialogue with it. Such a reality must be experienced in the DRC in general and in Kisangani in particular where some private university institutions are located. But the observation is that the latter do not communicate often and do not care about their image vis-à-vis the internal and external public. This is the case of the Free University of Kisangani, established in the city of Kisangani since 2015, which has a communicational deficit and whose information from this university institution does not reach all social layers of this urban entity.